Access to credit and its impact on welfare in Malawi - Diagne, Aliou; Zeller, Manfred (International Food Policy Research Institute, 2001)
Poor rural households in developing countries lack adequate access to credit. Many development professionals believe that this lack of credit has negative consequences for poor people’s agricultural productivity, food security, health, and overall household welfare. Improved access to credit, they argue, will help poor rural households engage in more productive income-generating activities both on and off the farm and raise their living standards. Community and member-based microfinance programs have thus enjoyed considerable political and financial support during the 1990s. Yet in Access to Credit and Its Impact on Welfare in Malawi, Aliou Diagne and Manfred Zeller argue that access to microcredit may not be an effective way of alleviating poverty if the necessary infrastructure and socioeconomic environment are lacking.